Judicial Inconsistency and the Rule of Law: A Critical Analysis of Constitutional Court Decision on Presidential Age Requirements in Indonesia - Mukarromah, Naafiatul; Pangestu, Fachri Hamzah; Basuki, Udiyo; Hudallah, Muhammad Fahrul (UIN Sunan Kalijaga Yogyakarta, 2024)
The Constitutional Court (Mahkamah Konstitusi) of Indonesia plays a pivotal role as the guardian of the Constitution and the protector of constitutional rights. However, the Court’s ruling in Decision No. 90/PUU-XXI/2023 concerning the age requirements for presidential and vice-presidential candidates has sparked public controversy due to its inconsistency with previous judgments on identical legal provisions. This study critically examines the inconsistency of the Constitutional Court’s reasoning and evaluates the decision’s conformity with the principles of the rule of law and judicial independence. Using a normative juridical method supported by a statute and case approach, the research analyzes primary legal materials, including Constitutional Court decisions, relevant legislation, and judicial ethics regulations. The findings reveal that Decision No. 90/PUU-XXI/2023 deviates from the Court’s prior stance, effectively creating a new legal norm beyond its constitutional mandate, thus blurring the boundaries between judicial review and legislative authority. Furthermore, the proven ethical violations by the Chief Justice have weakened public trust in the integrity of constitutional adjudication. This article argues that such inconsistency undermines the predictability and legitimacy of the Court’s jurisprudence, which are essential to the rule of law. The study contributes to the broader discourse on judicial accountability by emphasizing the need for a coherent interpretive framework and stronger ethical oversight mechanisms to preserve the integrity of Indonesia’s constitutional justice system.